A Trichome-Specific, Plastid-Localized Tanacetum cinerariifolium Nudix Protein Hydrolyzes the Natural Pyrethrin Pesticide Biosynthetic Intermediate trans-Chrysanthemyl Diphosphate - Li, Wei; Lybrand, Daniel B.; Xu, Haiyang; Zhou, Fei; Last, Robert L.; Pichersky, Eran (Frontiers in Plant Science, 2020)
Tanacetum cinerariifolium flowers synthesize six pyrethrins that function as effective insecticides. trans-Chrysanthemol is an early intermediate in the synthesis of the monoterpene moiety of pyrethrins. Previously, the pyrethrum enzyme chrysanthemyl diphosphate synthase (TcCDS) was shown to catalyze the formation of the prenyl diphosphate compound chrysanthemyl diphosphate (CPP) by condensing two molecules of dimethylallyl diphosphate (DMAPP). Later work also showed that with a low concentration of DMAPP, TcCDS can also remove the diphosphate group to give chrysanthemol. The removal of the phosphate groups from other prenyl diphosphates, such as DMAPP, isopentenyl diphosphate (IPP) and geranyl diphosphate (GPP), was previously shown to occur in two steps. In those cases, the first phosphate group is removed by a member of the Nudix hydrolase protein family, and the second by other unidentified phosphatases. These previously characterized Nudix proteins involved in the hydrolysis of prenyl diphosphates were shown to be cytosolic. Here we report that a plastidic Nudix protein from pyrethrum, designated TcNudix1, has high specificity for CPP and can hydrolyze it to chrysanthemol monophosphate (CMP). TcNudix1 is expressed specifically in the trichomes of the ovaries, where chrysanthemol is produced. TcNudix1 expression patterns and pathway reconstitution experiments presented here implicate the TcNudix1 protein in the biosynthesis of chrysanthemol.